Phased array system simulation - Honglei Chen; Gentile, Rick (2016 IEEE International Symposium on Phased Array Systems and Technology (PAST), 2016)
Phased array radar system development starts with the design and analysis of the antenna array. While the benefits of phased array systems are great, the corresponding complexity grows with the additional transmit and receive channels [1,2,3,4,5,6]. Large antenna arrays can involve complex designs that include subarrays and a variety of configuration options. Having a flexible system level model that can be used to design, measure and assess the performance of an antenna array before it is built is critical to avoid costly errors late in the design cycle. In addition, design analysis and "what if' exercises can be greatly simplified with the availability of simulation capabilities early in the design cycle. A simulation framework will be described that can be used to analyze beam patterns of the antenna arrays. It can also be used to explore geometry options, element spacing, tapering parameters, array thinning, and steering performance. The framework makes it possible to model failed or imperfect array elements, develop calibration techniques, and assess the impacts of mutual coupling among elements in the antenna array. Additionally, to assess the impacts of phased array design decisions in the context of overall system level performance, a more complete framework for modeling and simulation will also be described by which multi-domain, multi-function radar systems can be designed and analyzed.